2006
DOI: 10.1158/1541-7786.mcr-05-0261
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, a Key Event in Cancer Development

Abstract: Several recent studies have identified nuclear factor-KB as a key modulator in driving inflammation to cancers. Besides this transcription factor, essential in regulating inflammation and cancer development, an inflammatory microenvironment inhabiting various inflammatory cells and a network of signaling molecules are also indispensable for the malignant progression of transformed cells, which is attributed to the mutagenic predisposition of persistent infection-fighting agents at sites of chronic inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
760
2
19

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 946 publications
(792 citation statements)
references
References 207 publications
(297 reference statements)
11
760
2
19
Order By: Relevance
“…It may be a good model of inflammation-associated carcinogenesis, because H. pylori infection induces intense acute and chronic inflammatory reaction that may last for decades (Price, 1991;Dixon et al, 1996). Moreover, H.pylori infection, environmental exposures, host genetic susceptibility, or some combination of these factors can lead to increased expression of cytokines, growth factors and their receptors, which in turn promotes cellular proliferation (Coussens and Werb, 2002;Lu et al, 2006). In addition, free radicals are generated as by-products of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…It may be a good model of inflammation-associated carcinogenesis, because H. pylori infection induces intense acute and chronic inflammatory reaction that may last for decades (Price, 1991;Dixon et al, 1996). Moreover, H.pylori infection, environmental exposures, host genetic susceptibility, or some combination of these factors can lead to increased expression of cytokines, growth factors and their receptors, which in turn promotes cellular proliferation (Coussens and Werb, 2002;Lu et al, 2006). In addition, free radicals are generated as by-products of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated concentrations of H 2 O 2 , dependent upon diet, lifestyle, and other health factors (Halliwell et al, 2000), can be found in the bladder and lower urinary tract. Epidemiological studies indicate that chronic inflammatory diseases are associated with an increased risk of human malignancies (Lu et al, 2006), including bladder cancer (BlCa) (La Vecchia et al, 1991;Hofseth et al, 1996) and chemical toxicity/irritation.…”
Section: Include (−)-Epicatechin (Ec) and (−)-Epigallocatechin (Egc)mentioning
confidence: 99%
“…In the tumor microenvironment, various inflammatory cells, such as tumor-associated macrophages, are recruited to form a pro-tumor inflammatory environment. Inflammatory cells produce a variety of mediators, including growth factors, chemokines and cytokines, which induce tumor growth, invasion, and angiogenesis (5,6).…”
Section: Introductionmentioning
confidence: 99%